Alterações comportamentais e de músculo esquelético em modelo experimental da doença de Parkinson: efeito do treinamento em esteira - Janine Costa Ivo (2014)
Parkinson's disease is the second most common neurodegenerative disease in humans. Its etiology involves genetic and environmental factors triggering death of dopaminergic neurons in the substantia nigra, a nucleus associated with the control of movement, which results in motor symptoms of the disease. In clinical routine, exercise interventions have proven effective in promoting overall improvement in the physical condition of patients, and generate benefits to the brain. Studies indicate that skeletal muscle can be the primary mediator of the beneficial effects of regular exercise, since muscle contraction interfere with signaling pathways which regulate the metabolic and phenotypic changes, as well as the production of neurotrophic factors and interleukins. This study aimed to investigate whether changes in motor behavior , serum and muscle levels of neurotrophic factors and muscle ultrastructure in an experimental model of pre - cline stage Parkinson's disease by intranasal infusion of MPTP in Holtzman ( 1 mice - methyl - 4 - phenyl - 1 , 2,3,6 - tetrahydropyridine ) , and evaluate the effect of treadmill training on these changes . For analysis of motor behavior, tests paw print and open field were used. The animals exercised on a treadmill showed a significant increase of the step lengths and passed as well as the exploratory curiosity, when compared to the sedentary animals. The driving condition was not affected by MPTP. The trained animals showed a reduction in serum levels of BDNF but not GDNF. The neurotoxin caused a reduction in BDNF levels in serum and soleus muscle of sedentary animals, but not in trained animals, while levels of GDNF were not changed. Morphometric analysis in images of soleus muscle, obtained by transmission electron microscopy, revealed that exercise was able to promote an increase in the relative percentage of mitochondrial profiles and triads, and reduction in the percentage of mitochondrial profiles with structural changes. In the presence of MPTP, however , there was a higher incidence of altered mitochondria, both in sedentary animals as in trained animals, indicating that exercise did not prevent ultrastructural alterations in the soleus muscle. Infusion of MPTP also resulted in increased percentage of myofibrils and decreased percentage of triads in trained animals. This is the first study that demonstrates changes in skeletal muscle that precede the onset of motor symptoms in animal model for Parkinson's disease. The resultsprovide good prospects for further studies designed to determine the contribution of muscle structures associated with the progression of motor symptoms in the disease.